Clinical Effectiveness of Pre-hospital and In-hospital Optimized Emergency Care Procedures for Patients With Acute Craniocerebral Trauma - Wang, Lili; Wu, Rong (Frontiers in Surgery, 2022)
Abstract we conducted an observational study of 130 patients with acute craniocerebral injury admitted between May 2020 and May 2021. In this study, we observed and compared the time taken to arrive at the scene, assess the condition, attend to the patient and provide emergency care, the success rate of emergency care within 48 hours, the interleukin-6 (IL-6), interleukin-8 (IL-8) and intercellular adhesion molecule-1 (ICAM-1) after admission and 1 day before discharge, the National Institute of Health Stroke Scale (NIHSS) and the Short Form 36-item Health Survey (SF-36) after resuscitation and 1 day before discharge, and the complications of infection, brain herniation, central hyperthermia and electrolyte disturbances in both groups. We collected and statistically analyzed the recorded data. The results showed that the time taken to arrive at the consultation site, assess the condition, receive the consultation, provide first aid was significantly lower in the optimized group than in the regular group (P<0.05); the success rate of treatment was significantly higher in the optimized group than in the regular group (P<0.05). In both groups, IL-6, IL-8 and ICAM-1 decreased on the day before discharge compared with the day of rescue, with the levels of each index lower in the optimization group than in the regular group (P<0.05); the NIHSS scores decreased and the SF-36 scores increased on the day before discharge compared with the successful rescue in both groups, with the NIHSS scores in the optimization group lower than in the regular group and the SF-36 scores higher than in the control group (P<0.05 ). The overall complication rate in the optimization group was significantly lower than that in the regular group (P<0.05). This shows that optimising pre-hospital and in-hospital emergency care procedures can significantly shorten the time to emergency care for patients with acute craniocerebral injury, increase the success rate, reduce inflammation, improve neurological function and quality of life, reduce the occurrence of complications, and improve patient prognosis.